Effects of rate and frequency of applied p on crop yields, p uptake, and fertilizer p use-efficiency and its recovery in a groundnut-mustard rotation - Aulakh, M.S.; PASRICHA, N.S. (Cambridge University Press, 1999)
A field experiment was conducted for 5 years (1992/93–1996/97) on Tolewal sandy loam soil (Typic Ustochrepts) in the subtropical region of northwest India (Ludhiana), to evaluate the effect of four rates of fertilizer P (0, 20, 30 and 40 kg P2O5/ha) applied at three frequencies representing direct, residual and cumulative P treatments on crop yields, P uptake, fertilizer P-use efficiency and fertilizer P recovery by groundnut (Arachis hypogaea) and mustard (Brassica napus) grown in a rotation.Groundnut responded to an application of P up to 20 kg P2O5/ha when the preceding mustard crop did not receive fertilizer P. However, when the mustard received 40 kg P2O5/ha, the succeeding groundnut crop did not respond to additional P applied to it, but obtained the required P from that which was in the soil including the residue from the previous application. The mustard crop responded significantly (46%) to P up to 40 kg P2O5/ha rate but there was a much less response (13–27%) to residual P that was applied to the preceding groundnut. The differences between these two crops are due to differences in climate between the mustard and groundnut growing seasons and corresponding differences in soil conditions, and perhaps also to differences in the P-solubilizing abilities of the two crops. The results suggest that in groundnut–mustard rotations grown under these climatic conditions, a direct application of 40 kg P2O5/ha to mustard would suffice to meet the P needs of both crops. This would be the most efficient way of using fertilizer P, increasing P recovery and improving total biomass partitioning to mustard seed or groundnut pod yield.